Pre- and Post-treatment Serum BAFF Levels and BAFF Gene Polymorphisms in Patients with Graves' Disease. (2nd January 2023) - Dhaouadi, Tarak; Rojbi, Imen; Ghammouki, Sameh; Ben Nacef, Ibtissem; Adel, Meriem; Mekni, Sabrine; Khiari, Karima; Ben Abdallah, Taïeb; Sfar, Imen; Gorgi, Yousr
ABSTRACT: Background: B cell activating factor (BAFF), a crucial factor for B cell survival and differentiation, has been linked to several autoimmune conditions. The aim of this study was to evaluate the association of BAFF gene's polymorphisms with its serum levels and to assess their effect on Graves' disease (GD) susceptibility and presentation. Methods: Sixty-two GD patients and 152 healthy controls have been enrolled to investigate BAFF rs9514827 (−2841 T/C), rs1041569 (−2701 T/A) and rs9514828 (−871 C/T) gene's polymorphism by PCR-RFLP and serum BAFF level's kinetics under medical treatment by ELISA. Results: Median serum BAFF level at baseline was significantly higher in GD patients (841.7 pg/ml [685.23–1058.32]) comparatively to controls (495.75 pg/ml [383.17–595.7]), p = 7.29 E-25. A ROC curve was used to assess BAFF performances in GD diagnosis and revealed an AUC of 94.9% [0.919–0.979], p = 7.29 E-25. At a cutoff value of 654.9 pg/ml of BAFF at baseline, the sensitivity and the specificity were, respectively, 83.9% and 90.8%. BAFF level was significantly increased in smoking patients (1079.55 pg/ml [875.35–1203]) comparatively to nonsmokers (746.95 pg/ml [643.2–915.7]), p = 3.1 E-5. While −2841 T/C and −2701 T/A genotypes and alleles frequencies were similar between patients and controls, the −871*T allele was significantly more prevalent in patients (0.613) than in controls (0.477); p = .01, OR [95% CI] = 1.73 [1.13–2.65]. The three studied polymorphisms were not associated with serum BAFF level at baseline. Conclusion: Serum BAFF level is significantly increased in GD especially in smoking patients. rs9514828 − 871*T allele might be a susceptibility variant for GD.